Faktor yang Berhubungan dengan Stress Kerja pada Tenaga Kerja Bongkar Muat (TKBM) di Pelabuhan Nusantara Parepare - Sumiati; Septiyanti; Rahman (Window of Public Health Journal, 2025)
Job stress is a state in which people experience physical and mental breakdown due to work-related problems that they cannot solve. The purpose of this research was to determine the factors associated with work stress. This study applies a quantitative method with a cross-sectional design. The sample in this study was 168 people selected through accidental sampling technique. Data were collected through a questionnaire and a chi-square analysis was performed with a confidence level of 95 (α=0.05). The results of this study show that work stress on loading and unloading workers at Nusantara Parepare Port in 2023 shows that there is a significant relationship to the variables of length of service, psychosocial and work climate. This research suggests that employees should condition themselves adequately both physically and mentally before starting work.